Supplementing the Diet of Hybrid Grouper (Epinephelus fuscoguttatus ♀ × E. lanceolatus ♂) with Compound Acidifier Is a Good Way to Alleviate Poor Intestinal Growth Caused by High Levels of Cottonseed Protein Concentrate - Jiacheng Zhang; Hongjin Deng; Weixing Liang; Shuyan Chi; Beiping Tan; Xiaohui Dong; Shuang Zhang (Aquaculture Nutrition)
This study investigated the effect of adding the compound acidifiers on the intestine health of hybrid grouper (Epinephelus fuscoguttatus ♀ × E. lanceolatus ♂) fed diet with higher cottonseed protein concentrate (CPC). To assess the benefits of compound acidifiers helping CPC to replace more fish meal (FM) for hybrid grouper, five isonitrogen and isolipid experimental diets were formulated. The five diets consisted of a control diet (FM, 50%) and four experimental diets (27.5% FM, 27.27% CPC), each of which contained compound acidifiers to varying degrees (FCA0, FCA0.05, FCA0.1, and FCA0.2). Each diet was fed to three replicates of each group for 8 weeks. In the FCA0.05 group, the results demonstrated a statistically significant increase in protein efficiency ratio, lipid efficiency ratio, and the activity of digestive enzymes in the intestine (P<0.05). In the FCA0.05 group, there was a clearly enhanced expression of anti-inflammatory cytokines in the intestines (P<0.05). In the FCA0.1 group, there may be an increase in the expression of important genes involved in fatty acid metabolism in the intestinal (P<0.05). Appropriate compound acidifiers decreased the relative abundance of Vibrio and other harmful bacteria in the intestine flora that were brought by high CPC. In conclusion, when the hybrid grouper was given a diet containing more CPC, the FCA0.05 group was able to promote intestinal development, enhance digestive enzyme activity and feed consumption, raise antioxidant enzyme activity and anti-inflammatory factor expression, and improve intestinal health.